Sphincter-Sparing Anal Fistula Repair: Are We Getting Better?. Issue 10 (October 2017) - Sugrue, Jeremy; Mantilla, Nathalie; Abcarian, Ariane; Kochar, Kunal; Marecik, Slawomir; Chaudhry, Vivek; Mellgren, Anders; Nordenstam, Johan
Abstract : BACKGROUND: Sphincter-sparing repairs are commonly used to treat anal fistulas with significant muscle involvement. OBJECTIVE: The current study evaluates the trends and efficacy of sphincter-sparing repairs and determines risk factors for fistula recurrence. DESIGN AND SETTINGS: A retrospective review was performed at 3 university-affiliated teaching hospitals. PATIENTS: All 462 patients with cryptoglandular anal fistulas who underwent 573 sphincter-sparing repairs between 2005 and 2015 were included. Patients with Crohn's disease were excluded. MAIN OUTCOME MEASURES: The primary outcome was the rate of fistula healing defined as cessation of drainage with closure of the external opening. Risk factors for nonhealing were also analyzed. RESULTS: Five hundred three sphincter-sparing repairs were analyzed, whereas 70 were lost to follow-up. Two hundred twenty sphincter-sparing repairs (44%) resulted in healing, 283 (56%) resulted in nonhealing with a median follow-up of 9 (range, 1–125) months. The median time to fistula recurrence was 3 (range, 0–75) months with 79% and 91% of recurrences noted within 6 and 12 months. Patients treated with a dermal advancement flap, rectal advancement flap, or ligation of the intersphincteric tract procedure were less likely to have a recurrence than patients treated with a fistula plug or fibrin glue ( p < 0.001). Over time, there was a significantly increased use of the ligation of the intersphincteric tract procedure ( p < 0.001) and a significantly decreased use of fistula plugs and fibrin glue ( p < 0.001); healing rates improved accordingly. There were no significant differences in healing rates with respect to patient demographics, comorbidities, or fistula characteristics. LIMITATIONS: This study was limited by its retrospective design. CONCLUSIONS: Healing rates following sphincter-sparing repairs of cryptoglandular anal fistulas are modest, but have improved over time with the use of better surgical techniques. In this study, ligation of the intersphincteric fistula tract and flaps were superior to fistula plugs and fibrin glue; the former procedures are therefore favored. SeeVideo Abstract athttp://links.lww.com/DCR/A391 .